(untitled) (Journal of actual problems of jurisprudence, 2018)
In this article the author does not aim to develop recommendations for action on all issues of qualifications of fraud. But based on the study of current legislation, legal scholars and scholars of jurisprudence in this paper is an attempt to reveal the meaning and signs of fraud, consider the history of the development of norms about fraud in the legislation of Kazakhstan. Also analyze the elements of fraud. The author analyzed qualifying certain types of fraud. Disclosed criteria distinguish fraud from adjacent structures and civil crime. Key words: subject, object, crimes against property, fraud.